Hubungan Pengetahuan, Sikap, Tindakan Terhadap Iklan Rokok Dengan Perilaku Merokok Pada Remaja Di Wilayah Kelurahan Mokoau Kec. Kambu Tahun 2023 - Narti Narti; Hartati Bahar; Farit Rezal (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Cigarette advertising is a broadcast media both mass media and electronic media. Cigarette advertisements Linking cigarettes to a trendy, informal, confident, adventurous, and loyal image of friendship can influence smoking behavior. This study aims to explore the correlation between knowledge, attitudes, and actions towards cigarette advertisements and smoking behavior among adolescents in Mokoau Village, Kambu District in 2023. It employs quantitative analytical research with a cross-sectional approach conducted in Mokoau sub-district. The study population consists of 85 respondents, with a sample of 70 respondents determined using the Slovin formula and an accidental sampling technique. The researchers utilized a questionnaire as their data collection instrument. However, the findings indicated no significant correlation (p-value < 0.05) between knowledge, attitudes, actions towards cigarette advertisements, and smoking behavior among adolescents in the Mokoau Village area of Kendari City in 2023. Counseling should be carried out both in schools and in the community with anti-smoking programs. This program is carried out in the community, especially adolescents, providing information about the dangers of cigarettes for health.